Measurement of inclusive ep cross sections at high Q2 at √s = 225 and 252GeV and of the longitudinal proton structure function FL at HERA - Andreev, Vladimir; Buniatyan, Armen; Herbst, Matthew; Huber, Florian; Sauter, Michel David; Schöning, André; Schultz-Coulon, Hans-Christian (The European physical journal. C, Particles and fields, 2014)
Inclusive ep double differential cross sections for neutral current deep inelastic scattering are measured with the H1 detector at HERA.
Gesehen am 18.09.2020
Im Titel erscheint beim Begriff Q2 die Ziffer 2 hochgestellt und beim Begriff FL das L tiefgestellt